Examining the role of berAKHLAK core values and work ethic in shaping civil servant performance - Citrowiharyo, Atma Divendra; Nastiti, Rizky; Bachtiar, Yanuar; Daud, Ibrahim (Institute of Computer Science (IOCS), 2025)
This research investigates the impact of the BerAKHLAK Core Values—comprising Service-Oriented, Accountable, Competent, Harmonious, Loyal, Adaptive, and Collaborative principles—and work ethic on the performance of civil servants (Aparatur Sipil Negara/ASN) within the Banjarmasin City Government. Employing a quantitative approach, the study collected data from 201 civil servants using structured questionnaires, with the analysis conducted through regression analysis. The results indicate a contrasting effect of the two independent variables: the BerAKHLAK Core Values demonstrated a negative and significant influence on ASN performance, whereas work ethic showed a positive and significant influence. These findings highlight an intriguing dynamic, suggesting that while adherence to BerAKHLAK values may inadvertently constrain performance—potentially due to rigid interpretations or implementation challenges—strong work ethic consistently enhances employee output. The study underscores the importance of balancing value internalization with practical work behaviors to improve overall civil servant performance